The Effect of Competency, Work Discip line and Motivation on Employee Performance: TheCase of Coal Handling Facility and Main Mining Equipment Maintenance Sub-Division of PT. Bukit Asam Tbk. Tanjung Enim - Frenky Hidayat; Choiriyah Choiriyah; Yudha Mahrom (International Journal of Marketing & Human Resource Research, 2026)
This study aims to examine: (1) the simultaneous effect of competence, work discipline, and motivation on employee performance; and (2) the partial effect of each variable—competence, work discipline, and motivation—on employee performance. The research was conducted in the Coal Handling and Main Equipment Maintenance Subdivision of PT Bukit Asam Tbk, Tanjung Enim Mining Unit. This study uses an associative quantitative approach with competence, work discipline, and motivation as independent variables, and employee performance as the dependent variable. The sample consisted of 138 employees selected using cluster random sampling. Data were collected through questionnaires and supported by secondary data sources. The analysis was conducted using multiple linear regression. The results indicate that competence, work discipline, and motivation simultaneously have a significant effect on employee performance. Partially, competence has a significant effect on performance, while work discipline and motivation do not show a significant effec